Early Carboniferous ophiolite in central Qiangtang, northern Tibet: record of an oceanic back-arc system in the Palaeo-Tethys Ocean. Issue 4 (12th March 2018) - Zhang, Tian-Yu; Fan, Jian-Jun; Li, Cai; Xie, Chao-Ming; Wang, Ming; Wu, Yan-Wang; Xu, Meng-Jing; Xu, Wei; Liu, Jin-Heng; Luo, An-Bo
ABSTRACT: Zircon U–Pb dating of two samples of metagabbro from the Riwanchaka ophiolite yielded early Carboniferous ages of 354.4 ± 2.3 Ma and 356.7 ± 1.9 Ma. Their positive zircon ε Hf( t ) values (+7.9 to +9.9) indicate that these rocks were derived from a relatively depleted mantle. The metagabbros can be considered as two types: R1 and R2. Both types are tholeiitic, with depletion of high-field-strength elements (HFSE) and enrichment of large-ion lithophile elements (LILE) similar to those of typical back-arc basin basalts (BABB), such as Mariana BABB and East Scotia Ridge BABB. Geochemical and isotopic characteristics indicate that the R1 metagabbro originated from a back-arc basin spreading ridge with addition of slab-derived fluids, whereas the R2 metagabbro was derived from a back-arc basin mantle source, with involvement of melts and fluids from subducted ocean crust. The Riwanchaka ophiolite exhibits both mid-ocean ridge basalts- and arc-like geochemical affinities, consistent with coeval ophiolites from central Qiangtang. Observations indicate that the Qiangtang ophiolites developed during the Late Devonian–early Carboniferous (D3 –C1 ) in a back-arc spreading ridge above an intra-oceanic subduction zone. Based on our data and previous studies, we propose that an oceanic back-arc basin system existed in the Longmuco–Shuanghu–Lancang Palaeo-Tethys Ocean during the D3 –C1 period.